Brain death following ingestion of E‐cigarette liquid nicotine refill solution. Issue 9 (28th July 2020) - Scarpino, Maenia; Bonizzoli, Manuela; Lanzi, Cecilia; Lanzo, Giovanni; Lazzeri, Chiara; Cianchi, Giovanni; Gambassi, Francesco; Lolli, Francesco; Grippo, Antonello
Abstract: Background: The use of electronic cigarettes (e‐cigarettes) is very common worldwide. To date, an increase of nicotine intoxication following an accidental or intentional ingestion/injection of refill solution (e‐liquid) has been detected. Case: A 23‐year‐old man presented with sudden loss of consciousness, bradycardia, and respiratory muscle paralysis after intentional ingestion of e‐liquid. Early clinical data, brain computed tomography, and neurophysiological tests (electroencephalogram [EEG] and somatosensory evoked potentials [SEPs]) did not show features with a poor neurological prognostic meaning of an hypoxic encephalopathy. After 4 days, the patient showed bilateral loss of the pupillary reflex, and severe and cytotoxic edema was detected on brain magnetic resonance imaging. SEPs showed a bilateral loss of cortical responses and EEG a suppressed pattern. Nine days after the onset of coma, the patient evolved toward brain death (BD). Discussion: Because nicotine intoxication might cause respiratory muscle paralysis, without cardiac arrest (CA), it would be important to understand the mechanisms underlying brain damage and to take into account that the current neurological prognostic evidence for hypoxic–ischemic encephalopathy, based on data from patients who all experienced CA may not be reliable. Reporting cases of nicotine intoxication through e‐liquid is relevant in order to improve regulatory parameters for e‐liquid sale. Abstract : Electronic cigarettes (e‐cigarettes), based on the vaporization of e‐liquid, a solution composed of nicotine, vegetable glycerine, and propylene glycol, have become very common worldwide and can be easily purchased online, where virtual stores are poorly monitored. This is representing a relevant health problem in the last decade, because of the increase in cases of accidental or intentional poisoning through the ingestion and/or the injection of e‐liquid composed of high‐dose nicotine. We report a case of voluntary ingestion of e‐liquid refill that caused respiratory arrest causing coma and that in the following days evolved toward brain death. This case is the first with fatal outcome in the absence of concomitant cardiac arrest. The constant reporting of cases of nicotine intoxication through e‐liquid both accidental or intentional is an important goal in order to raise the awareness of the Food and Drug Administration in improving regulatory parameters for e‐liquid and in increasing the monitoring of online stores.